Importance of stabilization of the neonatal transport network in critically ill neonates. Issue 8 (August 2019) - Xu, Xiao-Jing; Li, Li-Na; Wu, Wen-Yan
Objective: This study aimed to investigate how to stabilize the condition of critically ill neonates within the neonatal transport network. Methods: A total of 243 critically ill newborns in four hospitals involved in the transport network were enrolled. The newborns were divided into the research and control groups. In the research group, medical staff underwent theoretical training, and neonatal intensive care unit (NICU) professionals participated and provided on-site guidance on delivery of high-risk infants. Delivery of high-risk neonates in the control group was conventionally managed in local hospitals, and neonates were transferred after a phone call to the NICU. Results: Gestational age and body weight were lower, and dexamethasone use was higher in the research group than in the control group. The proportions of neonates who underwent mask pressure, endotracheal intubation, pulmonary surfactant application, and chest compressions were higher, and those with dyspnea and nervous system abnormalities were lower in the research group than in the control group. Blood gas and sugar levels were better in the research group than in the control group. Conclusion: Strengthening professional training and participation of professional NICU staff in childbirth can improve the conditions of high-risk neonates and increase safety of their transportation.